COLLATERAL CONSTRAINTS AND THE CURRENT ACCOUNT: THEORY AND EVIDENCE. (10th September 2015) - Kunieda, Takuma; Okada, Keisuke; Shibata, Akihisa
Abstract : We investigate the impact of domestic financial frictions on the current account dynamics in Asian countries before and after the Asian financial crisis in 1997–1998 by introducing collateral constraints into the intertemporal current account approach. We examine six Asian countries. Before the crisis, collateral constraints significantly impact the current account in Korea, Malaysia, the Philippines, and Thailand, but after the crisis, they do not. Our study shows that the impact of domestic financial frictions on the current account changes before and after a financial crisis. ( JEL F32, F41)